A Contemporary Fairy Tale: García Márquez' "El rastro de tu sangre en la nieve" - Arnold M. Penuel (Studies in 20th & 21st Century Literature, 1995)
The pattern usually found in fairy tales is for the hero or heroine to struggle against, and finally overcome, what seem to be overwhelming odds, after which he or she lives happily ever after. This pattern, according to Bruno Bettelheim, is emblematic of the struggle required of every individual in real life in order to develop the maturity to cope with, and thrive in, the world. García Márquez' story, "El rastro de tu sangre en la nieve," whose dominant intertext is the fairy tale, turns this pattern on its head. Handicapped by privileged upbringing, cultural narcissism, and the necessity of adapting to the demands of a different culture, Billy Sánchez, the hero, or perhaps better, the antihero of "El rastro," utterly fails to master the challenges he meets; rather than rising to a higher level of maturity, in the end he reverts to an infantile way of coping with the world. A Colombian from Cartagena de Indias, Billy's inability to adapt to the French mode of being illuminates certain differences between Hispanic and French cultures. Implicit in the story of Billy's failure is the suggestion that to get along in today's interdependent world one needs a cosmopolitan education; knowledge of the ways of a single culture is simply not adequate preparation for life in the "global village."
Keywords: Gabriel García Márquez; el rastro de tu sangre en la nieve; fairy tales; Bruno Bettelheim; cope; coping; being; Hispanic culture; French culture; global